The Influence of Compensation, Motivation, and Work Discipline on Employee Performance from an Islamic Economic Perspective - Pratama, Andrean; Maulana, Hafizh; Farma, Junia (Universitas Syiah Kuala, 2025)
The Shopee Express Hub in Banda Aceh faces challenges in improving employee productivity and work quality. Variables such as compensation (salary and incentives), motivation (internal and external), and work discipline (adherence to rules and responsibilities for tasks) are considered significant factors in influencing employee performance. This study was conducted using a quantitative approach through the collection of primary data via a questionnaire distributed to Shopee Express Hub employees in Banda Aceh. The data analysis technique used was multiple regression to test the research hypotheses, and the data was processed using SPSS version 22. Based on the results of the study conducted using a t-test, it was concluded that compensation does not significantly influence employee performance. However, motivation was found to significantly influence employee performance, while work discipline also showed a significant impact on performance. Furthermore, the results of the F-test indicate that compensation, motivation, and work discipline simultaneously influence employee performance. Based on these findings, the researcher provides the following suggestions: the company should increase its attention toward employees by providing additional compensation as a form of recognition for their dedication, which can further motivate them to work harder. For the employees themselves, discipline is a very important factor in creating a healthy work environment. Therefore, awareness of company rules must be improved to foster better organizational performance.